Analisis usaha tani teh di Kabupaten Kulon Progo - Kurniaty, Tri (LPPM Universitas Pahlawan Tuanku Tambusai, 2024)
This study analyzes the potential of tea farming in Samigaluh District, Kulon Progo, which spans 100.33 hectares with a production output of 220.26 tons in 2021. Beyond being an agribusiness commodity, tea also supports the development of agro-tourism-based ecotourism. Farmers' average monthly income is Rp 2,142,027, with an R/C ratio of 5.11, indicating significant profitability. The use of Urea and Compost fertilizers is a key factor influencing production outcomes. Challenges include climate change, trade monopolies, and limited packaging innovation. Government support in technical training, agricultural technology access, and marketing strategies is essential to enhance the sustainability of tea farming. Further research is needed to address market and environmental challenges and strengthen institutional roles in supporting farmers' competitiveness in local and international markets.